2003
DOI: 10.1097/01.olq.0000091152.31366.e6
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence and Prevalence of Hepatitis C Virus Infection Among Sexually Active Non-Intravenous Drug-Using Adults, San Francisco, 1997–2000

Abstract: The absence of new HCV infections in this sample supports the hypothesis that the risk of sexual transmission of HCV is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 31 publications
2
31
1
1
Order By: Relevance
“…This study supports previous work that risky injection drug use practices result in the transmission of HBV or HCV [4,7,11,13,[34][35][36], and the longer one injects, in regards to age and duration, in a high risk population, the more likely the person will be infected [11-13, 37, 38]. However, sharing needles was not associated with HBV or HCV in this study, contrasting a previous study by our principal investigator [4], and others [13].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This study supports previous work that risky injection drug use practices result in the transmission of HBV or HCV [4,7,11,13,[34][35][36], and the longer one injects, in regards to age and duration, in a high risk population, the more likely the person will be infected [11-13, 37, 38]. However, sharing needles was not associated with HBV or HCV in this study, contrasting a previous study by our principal investigator [4], and others [13].…”
Section: Discussioncontrasting
confidence: 57%
“…Sexual behavior in noninjecting drug users may be influenced by stimulant drug activity, especially crack cocaine [17,21,[23][24][25][26], influencing the drug user to participate in risky sexual behaviors, resulting in increased risk for HIV, hepatitis B, and STDs. From our previous studies and others, there was no significant association found between HCV infection and sexual risk behaviors [4,34]. Transfusion-associated HCV has been documented [42].…”
Section: Discussionmentioning
confidence: 99%
“…14 In HIV-positive homosexual men, generally higher rates of HCV have been reported, ranging from 5.8% to 35.9%. 10,11,14 An epidemic of acute hepatitis C in HIV-positive homosexual men in London was recently reported, and it was speculated that these cases were sexually transmitted, perhaps related to a high rate of concurrent syphilis infection. 13 Another reason for suspecting that unprotected sex among HIV-positive men may be a higher risk setting for HCV transmission than among HIV-negative men is that individuals with HIV/HCV co-infection have higher HCV viral loads.…”
Section: Discussionmentioning
confidence: 99%
“…Masih terdapat pro kontra mengenai transmisi seksual virus hepatitis C. Beberapa studi mendapatkan bahwa risiko transmisi seksual hepatitis C memang ada, namun risiko tersebut rendah. [15][16][17] Adanya infeksi HIV dapat meningkatkan risiko transmisi seksual virus hepatitis C. Gabrielli dkk 10 dalam studi potong lintang mendapatkan prevalensi hepatitis C pada pasangan seksual pengguna narkotika suntik dengan koinfeksi HIV/HCV sebesar 9,5%. Pada kelompok pasangan seksual dengan status HIV positif didapatkan prevalensi hepatitis lebih tinggi dibandingkan dengan yang HIV negatif (28,6% vs 12,8%).…”
Section: Pendahuluanunclassified